Sputtering of a metal nanofoam by Au ions - Anders, Christian (2015)
Porous materials, such as nanofoams, may react differently to irradiation than compact targets. This is caused by the influence of the cavities on the evolution of collision cascades, but also by the differing heat conduction which affects the spike phase. Using molecular dynamics simulation we study the sputtering of a Au nanofoam by 10 keV Au projectiles, and compare to the sputtering of a compact Au target. These bombardment conditions lead to a strong contribution of spikes to the sputtering process. We find the foam to sputter considerably less than the compact target; the open structure of the foam prevents the build-up of strong collision spike regions at the surface, which are the major source of sputtering in the compact target. Also emission takes a longer time scale in the foam, as particles need to travel longer pathways to be emitted. On the other hand, the molten phase is more extended in the foam and also exists for a longer time; this is caused by the reduced heat conductivity in this material.